Computer Models of Electrical Impacts on Adjacent Lines of Traction Systems (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The article develops computer models of electrical impacts on the adjacent lines of the traction system 20 kilometers from the Chinaz station of the Tashkent-Syrdarya road. Studies have shown that the greatest value of the induced voltage occurs in the middle of the line when the beginning and end of the adjacent line are grounded, but its value does not exceed 8 V. It was also determined that to reduce the value of the induced voltages from the electrical impact of the thrust system, it is sufficient to ground the investigated side line from both sides, and if the value of the induced voltage in this case is higher than 25 volts, the line should be grounded in several places, including in the middle of it.